A note on the DML distribution and catches of Sepia bertheloti and Sepia officinalis (Cephalopoda: Sepiidae) on the saharan bank - Hernández García, Vicente; Castro, J.J. (1994)
Cephalopod species were sampled from commercial catches in Saharan Bank waters during August 1989 and March 1990. Biological and fishing data were recorded. In this paper we analyse sorne of the biological data with respect to Sepia officinalis and S. bertheloti in the fishing Area 34: 1.3, above aU the data relative to size distribution and migration pattem of both species. Sepia officinalis was important in catches only second in importance to Octopus vulgaris, whereas S. bertheloti was relatively circumstantial in catches. Toe size distribution of Sepia officinalis was similar between both periods, but S. bertheloti showed a larger range of sizes in the Summer. On the other hand, while Sepia bertheloti migrates to shallow waters to spawn during Summer, S. officinalis seems to do so during Winter and Sprin 9